The Effect of Using an Autofeeder on Vannamei Shrimp (Litopenaeus vannamei) Growth in Intensive Ponds at Cv. Cemara Sewu Sumber Rejeki, Cilacap - Andreas Eka Saputra -; Kasprijo kasprijo; Purnama Sukardi (PT. Artha GenetikaLab Indonesia, 2024)
The use of automatic feeding equipment can increase the productivity of vannamei shrimp cultivation and harvest yields. This research aimed to determine which of the three feeding methods (manual, 120° autofeeder, and 360° autofeeder) produces greater growth and production results for vannamei shrimp. The shrimp used came from Sura Tani Pemuka which were stocked from 23-25 July 2022 at PL (post larval) age 11. When using a 360° autofeeder with a total area of 5,880 m2 and a density of around 169 individuals/m2. When using a 120° autofeeder with a total area of 2,840 m2 and a density of around 166 fish/m2. The manual method is used with a total area of 2,500 m2 and a density of around 187 individuals/m2. The research method was carried out by means of descriptive observation and analysis. Data collection was carried out during shrimp sampling activities, checking water quality, and harvesting. The research results showed that the use of a 360° autofeeder, 120° autofeeder, and manual resulted in sequential growth performance including: survival rates of 39.37%, 51.47%, and 32.47%; average weight growth of 21.53 gr/head, 17.47 gr/head, and 10.12 gr/head; daily weight growth of 0.31 gr/day, 0.25 gr/day and 0.16 gr/day; and, feed conversion ratios were 1.84, 1.73 and 2.23. The harvest results achieved using the 360° autofeeder, 120° autofeeder, and manual method reached 4558.32 kg, 3670.18 kg, and 1294.965 kg, respectively.